(untitled) (Horizon Multidisciplinary Scientific Journal, 2026)
The article presents and justifies the basic principles of a new technology for the integration of heterogeneous data. It is known that in modern corporations a significant amount of information is collected, which is growing exponentially. The relevance of manipulating this type of data is further increased by its heterogeneity. The article studies the main characteristics of heterogeneous data and the problems of their integration. The classification scheme of data integration technologies is analyzed and relevant recommendations are put forward. At the same time, models for building a general technological scheme for data integration in information systems are studied. In this regard, the presented technology includes a number of new mathematical object models, methods and software tools for presenting and manipulating data. This technology, which combines mathematical models and tools, provides compatibility with a wide range of modern tools and modern standards for the development of information systems.